2011
DOI: 10.1007/s12011-011-9160-4
|View full text |Cite
|
Sign up to set email alerts
|

Excess Dietary Sodium Selenite Alters Apoptotic Population and Oxidative Stress Markers of Spleens in Broilers

Abstract: Three hundred 1-day-old avian broilers were fed on a basic diet (0.2 mg/kg selenium) or the same diet amended to contain 1, 5, 10, and 15 mg/kg selenium supplied as sodium selenite (n = 60/group). In comparison with those of 0.2 mg/kg selenium group, the percentages of annexin V-positive splenocytes were increased in 5, 10, and 15 mg/kg selenium groups. TUNEL assay revealed that apoptotic cells with brown-stained nuclei distributed within the red pulp and white pulp of the spleens with increased frequency of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, it should be noted that the splenic apoptosis in TN and HS groups is 3.5% and 6.6%, respectively. Additionally, several reports found that different stressors increase the apoptosis of the spleen from approximately 4% (control group) to 6% (stressed group) in chickens [36][37][38]. Zhao et al [39] showed that the apoptosis of the spleen in the control group was 0.5%, and the stress induced by the toxin only increased the apoptosis of the spleen to 2% in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the splenic apoptosis in TN and HS groups is 3.5% and 6.6%, respectively. Additionally, several reports found that different stressors increase the apoptosis of the spleen from approximately 4% (control group) to 6% (stressed group) in chickens [36][37][38]. Zhao et al [39] showed that the apoptosis of the spleen in the control group was 0.5%, and the stress induced by the toxin only increased the apoptosis of the spleen to 2% in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2014) reported that in the spleen of chickens the catalase activity was decreased in cadmium group according to the control and selenium groups. Peng et al (2012) found that catalase activity in the spleen tissue of chickens fed 10 mg/kg and 15 mg/kg selenium‐containing sodium selenite decreased with time depending on the control group. In our study, it was conducted that catalase immunoreactivity was intense in the spleen of the long‐legged buzzard.…”
Section: Discussionmentioning
confidence: 99%
“…The depression of the thymic lobule at 0.1 mg and 0.5 mg selenium (sodium selenite) supplementation was previously revealed by histological observation [15], but our measurements did not confi rm these results. Peng et al [16] reported that supplementation of 1 mg of Se (sodium selenite) in 1 kg of feed did not infl uence the percentage of apoptotic splenocytes. On the contrary, it signifi cantly decreased the relative weight of bursa and the number of lymphocytes in lymphoid nodules [17], but by pathological observation no obvious changes in the BF were observed.…”
Section: Discussionmentioning
confidence: 99%